Design Principles for a Special Education Center for Children on Autism Spectrum Disorder - Merve Kavaz (Iconarp International Journal of Architecture and Planning, 2025)
Autism Spectrum Disorder (ASD) expresses different usage of communication, application of language and stereotypic behavior. ASD continues lifelong. Therefore, good design quality and special education is essential for individuals who are diagnosed with ASD. The suitable design of special education center for ASD will help children on the spectrum to learn and gain communication skills in comfortable environments. However, design for autism is an overlooked topic by design researchers, interior architects. This research aims to fill the gap in the literature of design for ASD. The qualitative research is applied in the research to comprehend design problems and solve it by new understanding of design. In this study, 6 autism experts’ idea were taken in the meetings to design better autism centers for individuals on the spectrum. Participants of the study shared their observation of autism centers and approach for better autism centers. Depending on the repetitive view of problems and solutions, some research codes were achieved to have common sense of autism design. Moreover, special education center in the USA was visited to analyze more deeply. Main problem of special education design is crowded classrooms which doesn’t help students to self-regulate. Also being unaware of ASD and its relation to the design creates ignorance to design for ASD. Depending on the interviews and observation of autism center, solution for design problems are displayed. By this way, design set-up can be made to create autism friendly centers.